Glutathione S-Transferase T1 and M1: Gene Sequence Variation and Functional Genomics - Moyer, Ann M.; Salavaggione, Oreste E.; Hebbring, Scott J.; Moon, Irene; Hildebrandt, Michelle A.T.; Eckloff, Bruce W.; Schaid, Daniel J.; Wieben, Eric D.; Weinshilboum, Richard M. (Clinical cancer research, 2007)
Purpose: The glutathione S -transferases (GSTs) catalyze the glutathione conjugation of reactive electrophiles, including carcinogens and many antineoplastic drugs. GSTT1 and GSTM1 are polymorphically deleted, but the full range of genetic variation in these two genes has not yet been explored. We set out to systematically identify common polymorphisms in GSTT1 and GSTM1 , followed by functional genomic studies. Experimental Design: First, multiplex PCR was used to determine GSTT1 and GSTM1 copy number in 400 DNA samples (100 each from 4 ethnic groups). Exons, splice junctions, and 5′-flanking regions (5′-FR) were then resequenced using DNA samples that contained at least one copy of GSTT1 or GSTM1 . Results: Gene deletion frequencies among ethnic groups were from 33.5% to 73.5% for GSTT1 and from 50.5% to 78.0% for GSTM1. GSTT1 deletion data correlated with the results of mRNA microarray expression studies. The 18 single nucleotide polymorphisms (SNP) observed in GSTT1 included three nonsynonymous coding SNPs (cSNPs) and one single-nucleotide deletion, whereas the 51 GSTM1 SNPs included two nonsynonymous cSNPs. Two of the GSTT1 nonsynonymous cSNPs resulted in decreases in levels of immunoreactive protein to 56% and 12% of wild type (WT), whereas those in GSTM1 resulted in modest increases in protein levels. Reporter gene assays showed that one GSTT1 5′-FR haplotype, with a frequency of 32% in African-American subjects, resulted in an increase in transcription in JEG-3 cells to 351% of that for the WT sequence, and one GSTM1 5′-FR haplotype resulted in an increase in transcription in JEG-3 cells to 129% of WT. Conclusions: These observations suggest that functionally significant pharmacogenomic variation beyond GSTT1 and GSTM1 gene deletion may contribute to carcinogenesis or individual variation in antineoplastic drug therapy response.